The Account of the Death of King Wladyslaw IV Vasa in Merkinė on 20 May 1648 (ed. and translated from Latin into Lithuanian by Mintautas Čiurinskas) - Čiurinskas, Mintautas (Senoji Lietuvos literatūra, 2024)
-